Overview of Particle Accelerator Physics in South America: A Systematic Review of Regional Contribution and Collaboration Networks - Sánchez Rosas, Luis Junior (2023)
The landscape of particle accelerator physics in South America has been the subject of a systematic review that analyses the regional contribution and collaborative networks in this field. The research focuses on the role South American countries play in the development and research of particle accelerators, highlighting both the achievements and challenges facing the region. The review highlights the importance of international collaboration in particle accelerator physics, evidencing how South American scientists and institutions have established connections and alliances with research centers around the world. These collaborations have not only enabled access to advanced technologies and knowledge but have also contributed to the exchange of ideas and the development of scientific capacities in the region. This systematic review comprehensively examines the state of particle accelerator physics in South America, assessing regional contributions, collaborations, and challenges through the analysis of 797 articles collected from the Scopus (716 articles) and Web of Science (230 articles) databases. The study highlights the leadership of Brazil and Argentina as major players in the region, emphasizing their significant contributions to advancement and research in this field. The research reveals how international collaboration has been instrumental, in allowing South American scientists and institutions to forge strategic alliances with global research centers. These synergies have facilitated access to cutting-edge technologies and the exchange of knowledge, significantly boosting regional scientific development. Emblematic projects and key technological advances are highlighted, underscoring South America's potential in particle physics. Finally, critical challenges are identified, such as the need to increase investment in infrastructure and talent training. The study suggests strengthening intra-regional and international collaboration networks to overcome these barriers. In conclusion, this review provides a comprehensive perspective on particle accelerator physics in South America, highlighting the achievements, challenges, and the vital importance of international collaboration in advancing this essential scientific field.